HUBUNGAN DUKUNGAN SUAMI DENGAN KEPATUHAN KUNJUNGAN ANC - Nurul Fitriyah; Danti, Renita Rizkya; Muhammad Al Amin (WOMB Midwifery Journal, 2023)
The maternal mortality rate in 2020 has increased partly due to pregnant women's non-compliance with ANC check-ups. According to data from the Ministry of Health of the Republic of Indonesia, Indonesia did not reach the target of 93.3 percent of ANC visits. This study aims to determine the relationship between compliance of pregnant women in conducting antenatal care (ANC) in the working area of the Wongsorejo Health Center with husband support. Retrospective design was used in this research methodology, using a purposive sampling, the total population was 139 people and the sample size was 58 respondents. Visit data from the MCH book from June to August at 2022 was used as a research instrument. Wilcoxon statistical test was used for data analysis to obtain data on differences between the two groups. The results showed that out of 58 respondents, or 32 people (55.2%), reported that they had strong husband support. Of these pregnant women, 27 people (46.6%) made compliant ANC visits. In the working area of Puskesmas Wongsorejo, there is a significant relationship between husband support and adherence to ANC visits, as indicated by a significance value of 0.025 obtained from the Wilcoxon statistical test. It is suggested that it can provide information and add insight into the importance of support and involvement of husbands to pregnant women in antenatal care (ANC) checks.